Testosterone levels positively linked to muscle mass but not strength in adult males aged 20–59 years: a cross-sectional study - Zhang, Wei; Cui, Zhaohui; Shen, Dayong; Gao, Li; Li, Qingyun (Frontiers in Physiology, 2025)
BackgroundThe relationship between testosterone levels and muscle mass and strength remains contentious. This study aimed to explore the relationship among total serum testosterone levels, muscle mass, and strength in young to middle-aged adults.MethodsThe analysis included 4,495 participants (age 39.2 ± 0.2 years, mean ± SE) from the National Health and Nutrition Examination Survey conducted between 2011 and 2014. Weighted regression models were used to assess the association of testosterone levels with muscle mass and strength.ResultsFor male participants, log2-transformed testosterone levels were positively associated with appendicular lean mass adjusted for body mass index (β: 0.05, 95% confidence interval [CI]: 0.03–0.07, P < 0.001) and negatively associated with low muscle mass (odds ratio: 0.40, 95% CI: 0.24–0.67, P = 0.006). However, no significant association was found between testosterone levels and grip strength (β: 1.16, 95% CI: 0.26 to 2.58, P = 0.086) or low muscle strength (odds ratio: 0.51, 95% CI: 0.25–1.04, P = 0.059). For female participants, no significant association was observed between testosterone levels and muscle mass (β: 0.01, 95% CI: 0.02 to −0.01, P = 0.294) or muscle strength (β: 0.14, 95% CI: 0.45 to 0.73, P = 0.508). Restricted cubic spline analysis revealed a linear relationship between total testosterone levels and appendicular lean mass adjusted for body mass index in male participants (nonlinear: P = 0.367).ConclusionOur study indicates that testosterone levels are positively associated with muscle mass but not with muscle strength in young to middle-aged males.